2020
DOI: 10.1002/jso.25981
|View full text |Cite
|
Sign up to set email alerts
|

Importance of resection for locoregional disease control in Masaoka stage IVA thymic neoplasms

Abstract: Background and Objectives It is unclear if a specific strategy for simultaneous treatment of primary thymic neoplasms and pleural metastases confers benefit for Masaoka stage IVA disease. We reviewed our experience with thymic neoplasms with concurrent pleural metastases to identify factors influencing outcomes. Methods Records of patients who presented with stage IVA thymic neoplasms from 2000 to 2018 were assessed. Multivariate Cox proportional hazards analyses were completed to determine predictors of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Studies have indicated that surgery is a prognostic factor for thymic epithelial tumors, regardless of whether they are thymoma or thymic carcinoma. Complete resection can improve the survival rate, 27-29 which is consistent with our results. Additionally, a Japanese study 2 retrospectively analyzed 1320 patients with thymic epithelial tumors and revealed that debulking surgery is valuable for invasive thymoma, so for invasive thymoma, even if it cannot be completely removed, surgeons still need to remove as much tumor tissue as possible.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have indicated that surgery is a prognostic factor for thymic epithelial tumors, regardless of whether they are thymoma or thymic carcinoma. Complete resection can improve the survival rate, 27-29 which is consistent with our results. Additionally, a Japanese study 2 retrospectively analyzed 1320 patients with thymic epithelial tumors and revealed that debulking surgery is valuable for invasive thymoma, so for invasive thymoma, even if it cannot be completely removed, surgeons still need to remove as much tumor tissue as possible.…”
Section: Discussionsupporting
confidence: 92%
“…The assessment of resectability is mostly based on the surgeon expertise, but may be complex, even if the 8th TNM staging allows a better definition of resectable anatomical structures (stage IIIA). Ultimately, stage IV disease does not mean that the tumour is not amenable to complete surgical resection, especially in the setting of pleural implants [19,20]. Multidisciplinary tumour board is then highly valuable at any stage of the disease.…”
Section: Multidisciplinary Tumour Board Is Mandatorymentioning
confidence: 99%
“…Several retrospective analyses have shown that surgery is an effective treatment for pleural metastases from thymoma (simultaneous pleural metastases and heterochronic pleural metastases) and can improve patient survival. [7][8][9] Local radiotherapy for pleural metastases has also achieved good local control. [10][11][12] The combined modality of surgery, chemotherapy, and radiotherapy has been shown to improve the survival of patients with pleural metastases from thymoma.…”
Section: Introductionmentioning
confidence: 99%